Answer:
Below.
Step-by-step explanation:
- tan 2x = -2tanx / (1 - tan^2x)
Using the identity tan^2x = sec^2x - 1 and substituting for tan^2x:
- tan 2x = -2 tanx / (1 - (sec^2x - 1))
= 2 tanx / ( - 1(sec^2x + 2))
= 2 tan x / (sec^2 x - 2)
Step-by-step explanation:
1 Find common denominator (lower numbers)
2 add numerators(top numbers)
3 put the numerator over the denominator
ex 3/4+2/8
3x2=6,4x2=8
3/4=6/8
6/8+2/8=8/8 or 1
0.362 in expanded form is 0.3 + 0.06 + 0.002
If 3+4 = 7 and 6+7 = 7 leads to 3+4 = 6+1, then you are using the transitive property. In general the property says that if a = b and b = c, then a = c.
Answer:
ax²+bx+c
ax²+bxy+cy²
Step-by-step explanation:
A quadratic expression is one where the maximum degree of the variable or variables ( in case of more than one variable the sum of the degree of the variables in a single term considered) is 2.
For example:
A quadratic expression of a single variable is ax²+bx+c {Where a, b, and c are the arbitrary constants}
A quadratic expression with two variables is ax²+bxy+cy² {Where a, b, and c are the arbitrary constants}
And, a quadratic expression with three variables is ax² +by² +cz² +dxy +eyz +fzx {Where a, b, c, d, e, f are the arbitrary constants} (Answer)